Composition of medium and large-sized mammals in two protected areas of the Atlantic Forest in the central western mesoregion of Paraná state, Brazil - Alan Deivid Pereira; Sergio Bazilio (Revista de Biologia Neotropical, 2023)
There is a significant lack of information on the diversity of medium- and large-sized mammal species in heavily anthropologically altered regions, such as the Atlantic Forest of Southern Brazil. Biodiversity inventories play a crucial role in developing conservation and mitigation strategies at the local and regional scales. In this study, we conducted the first assessment of medium- and large-sized mammal species in two protected areas of the Atlantic Forest in the Central Western Mesoregion of Paraná State, Brazil. Sampling took place between September 2021 and September 2022 in Estação Ecológica Municipal de Roncador (EEMR) and Parque Municipal Miguel Pereira (PMMP) in Roncador City, PR. Using 180 h of active research and 64,800 h of camera trapping, we identified 27 species from 15 families and seven orders, with 40% of the recorded mammal species being endangered at the state, national, or international level. We also found two exotic and one domestic species in the protected areas. Our results improve our understanding of the southern Brazilian fauna, highlighting the importance of the protected areas EEMR and PMMP as refuges for medium- and large-sized mammals in the Central Eastern-Western Mesoregion of Paraná State.